Kepemimpinan Allah yang di Tunjukan Melalui Debora dan Barak - Karta, Endang Satria; Runesi, Serly Monita; Bambangan, Malik (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This article explains about Deborah's leadership as reflected in the narrative with Barak in the Book of Judges chapter 4 verses 1 to 24. Deborah was a woman chosen by God to lead the Israelites against the oppression carried out by King Jabin and the army under the leadership of Sisera. In this story, Deborah shows that a true leader must have strong faith, courage in making decisions, and wisdom in giving guidance. Although Barak had doubts at first, he eventually obeyed Deborah's orders with the belief that God would give him victory. Deborah's leadership teaches us that a leader does not only depend on their strength or position, but also on obedience to God and the ability to collaborate with others. This article also discusses how Deborah's leadership principles can be applied in our lives today, both in the church, society, and the workplace. The main message is that good leaders are those who have faith, courage, wisdom, and the ability to build solid cooperation.